2009
DOI: 10.2166/wst.2009.067
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and elimination of antibiotics at four sewage treatment plants in Japan and their effects on bacterial ammonia oxidation

Abstract: The occurrence and elimination of seventeen antibiotics (three macrolides: azithromycin, clarithromycin and roxithromycin; five quinolones: ciprofloxacin, enrofloxacin, levofloxacin, nalidixic acid and norfloxacin; five sulfonamides: sulfadimethoxine, sulfadimizine, sulfamerazine, sulfamethoxazole and sulfamonomethoxine; and others: tetracycline, lincomycin, salinomycin and trimethoprim) were investigated at four full-scale sewage treatment plants in Japan. The highest concentration was recorded for clarithrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
44
2
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(53 citation statements)
references
References 13 publications
5
44
2
2
Order By: Relevance
“…Ganciclovir and ribavirin were below the quantification limits in the influent, whereas the other antivirals were not detected in the wastewater (Table S1, Supporting material). This result was quite different from previous reports for wastewater in Japan and Europe in which oseltamivir and oseltamivir acid were frequently detected (Fick et al, 2007;Ghosh et al, 2009Ghosh et al, , 2010aPrasse et al, 2010;Soderstrom et al, 2009;Singer et al, 2008;Slater et al, 2011). In addition, abacavir, lamivudine, nevirapine, penciclovir, stavudine, and zidovudine were detected at several to hundreds of ng L −1 in the wastewater of Germany (Prasse et al, 2010) whereas the concentrations of lamivudine and nevirapine were approximately 1 μg L −1 in treated wastewater in Kenya (Koreje et al, 2012).…”
Section: Distribution and Behavior Of The Antiviral Drugs In The Wastcontrasting
confidence: 86%
See 2 more Smart Citations
“…Ganciclovir and ribavirin were below the quantification limits in the influent, whereas the other antivirals were not detected in the wastewater (Table S1, Supporting material). This result was quite different from previous reports for wastewater in Japan and Europe in which oseltamivir and oseltamivir acid were frequently detected (Fick et al, 2007;Ghosh et al, 2009Ghosh et al, , 2010aPrasse et al, 2010;Soderstrom et al, 2009;Singer et al, 2008;Slater et al, 2011). In addition, abacavir, lamivudine, nevirapine, penciclovir, stavudine, and zidovudine were detected at several to hundreds of ng L −1 in the wastewater of Germany (Prasse et al, 2010) whereas the concentrations of lamivudine and nevirapine were approximately 1 μg L −1 in treated wastewater in Kenya (Koreje et al, 2012).…”
Section: Distribution and Behavior Of The Antiviral Drugs In The Wastcontrasting
confidence: 86%
“…Besides, antivirals may produce resistance strains of pathogens in human and animals, which are of particular concerns (Hauser et al, 2011;Kiso et al, 2004;Olsen et al, 2006). It has been reported that Japan has a high rate of emerging resistance to oseltamivir, probably because it is the country where oseltamivir is used most (Ghosh et al, 2009;Soderstrom et al, 2009). In addition, oseltamivir in the environment may also impact the bacterial community structure (Caracciolo et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1970, the first report on pharmacologically active compounds in the water environment was published (Gosh et al, 2009), but the presence of drugs in the environment became an emerging concern only in the mid-1990s, when new analytical technologies were available (Homem, Santos, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…As antibiotics are highly bioactive compounds, there are serious concerns over their role in enhancing antibiotic resistance among pathogenic bacteria (Gosh et al, 2009), rendering current antibiotics ineffective in the treatment of numerous diseases (Homem, Santos, 2011). Antibiotics can also affect the endocrine system of fish and be toxic to algae and invertebrates (Guinea et al, 2009a(Guinea et al, , 2009b.…”
Section: Introductionmentioning
confidence: 99%